From slow repetition to awkward omission : Economic, efficient, and precise language use in bilingual formal meetings - Koskela, Merja; Pilke, Nina (De Gruyter, 2014)
This article explores how linguistic resources from two local languages, Finnish and Swedish, are used in expert presentations in bilingual formal meetings and how they function with respect to the three ideal criteria of professional communication: economy, efficiency, and precision. Based on the results, the article suggests a typology of bilingual action for bilingual formal meetings. While economic language use has to do with the time used for getting something done, efficiency, covers relevant, concise, and focused language use and precision is connected with ways of presenting a full depiction of the issues discussed. The typology suggests six types of bilingual action that interact closely depending on the context. The findings underline the importance of documentation and open discussion of organization-level practices in guiding bilingual action as an intentional and goal-oriented practice in professional contexts. The typology of bilingual action suggested in this article can be used when introducing the practices of bilingual meetings to new participants.
Keywords: formal meeting; bilingual action; professional communication; kokoukset; kaksikielisyys; talous; tehokkuus; tarkkuus; fi=Viestintätieteet|en=Communication Studies|